WHF IASC Roadmap on Chagas Disease - Echeverría, Luis Eduardo (2020)
Background: Chagas Disease is a neglected tropical disease caused by the protozoan Trypanosoma cruzi, with some of the most serious manifestations affecting the cardiovascular system. It is a chronic, stigmatizing condition, closely associated with poverty and affecting close to 6 million people globally. Although historically the disease was limited to endemic areas of Latin America recent years have seen an increasing global spread. In addition to the morbidity and mortality associated with the disease, the social and economic burdens on individuals and society are substantial. Often called the 'silent killer', Chagas disease is characterized by a long, asymptomatic phase in affected individuals. Approximately 30% then go on develop chronic Chagas cardiomyopathy and other serious cardiac complications such as stroke, rhythm disturbances and severe heart failure. Methods: In a collaboration of the World Hearth Federation (WHF) and the Inter-American Society of Cardiology (IASC) a writing group consisting of 20 diverse experts on Chagas disease (CD) was convened. The group provided up to date expert knowledge based on their area of expertise. An extensive review of the literature describing obstacles to diagnosis and treatment of CD along with proposed solutions was conducted. A survey was sent to all WHF Members and, using snowball sampling to widen the consultation, to a variety of health care professionals working in the CD global health community. The results were analyzed, open comments were reviewed and consolidated, and the findings were incorporated into this document, thus ensuring a consensus representation. Results: The WHF IASC Roadmap on Chagas Disease offers a comprehensive summary of current knowledge on prevention, diagnosis and management of the disease. In providing an analysis of 'roadblocks' in access to comprehensive care for Chagas disease patients, the document serves as a framework from which strategies for implementation such as national plans can be formulated. Several dimensions are considered in the analysis: healthcare system capabilities, governance, financing, community awareness and advocacy. Conclusion: The WHF IASC Roadmap proposes strategies and evidence-based solutions for healthcare professionals, health authorities and governments to help overcome the barriers to comprehensive care for Chagas disease patients. This roadmap describes an ideal patient care pathway, and explores the roadblocks along the way, offering potential solutions based on available research and examples in practice. It represents a call to action to decision-makers and health care professionals to step up efforts to eradicate Chagas disease.